"M" line: New anatomical landmark for the maxillary sinus natural ostium. (27th January 2020) - Leite, Janaina Gonçalves da Silva; Nogueira, Joao Flavio; Pallanch, John; da Costa, Ticiana Cabral; Feijão, Moisés Ximenes; Querido, Raquel de Sousa Lobo Ferreira; Cavalcante, Maria Luzete Costa
Abstract: Objective: Describe a reliable anatomical landmark that can be used to locate the maxillary sinus natural ostium (MSNO) during endoscopic surgery, even if the uncinate process is preserved. Design: Descriptive anatomical. Setting: An anatomical and radiological study was performed to evaluate the consistency of the landmark, denominated "M" line. Subjects and Methods: Dissections were performed in 57 cadaver heads (114 sides). In addition, 73 computerised tomography (CT) scans (146 sides) of patients with chronic inflammatory sinonasal disease were analysed using a three‐dimensional (3D) reconstruction computer program. Results: The "M" line crossed the MSNO in 112 dissected sides (98.2%) and 140 sides at CT 3D reconstruction (95.9%). Conclusion: The "M" line is a reliable anatomical landmark for predicting MSNO location. As such, it could improve and facilitate endoscopic sinus surgery, using traditional, minimally invasive or uncinate preserving techniques.